2021
DOI: 10.1155/2021/6625761
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Sun Protection Interventions Delivered to Adolescents in a Secondary School Setting: A Systematic Review

Abstract: Aim. The aim of this systematic review is to summarise the evidence of the effectiveness of interventions targeted to adolescents (13 to 18 years inclusive) and delivered in a secondary school setting with the purpose of improving sun protection behaviour, reducing ultraviolet radiation (UVR) exposure, and/or improving physiological outcomes related to UVR exposure (such as erythema or naevi development). Methods. Peer-reviewed journal articles were identified from seven database searches (Cochrane, Embase, CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…The best opportunities for reducing the frequency of skin cancer are in primary prevention interventions that reduce harmful sun exposure, thereby reducing DNA damage and potential skin cancer development. The available evidence suggests that young people are an important group on which to focus efforts, and adolescents, in particular, have been neglected in sun protection initiatives [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The best opportunities for reducing the frequency of skin cancer are in primary prevention interventions that reduce harmful sun exposure, thereby reducing DNA damage and potential skin cancer development. The available evidence suggests that young people are an important group on which to focus efforts, and adolescents, in particular, have been neglected in sun protection initiatives [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skin cancer prevention interventions for adolescents have been less commonly investigated than those for children and adults. A recent systematic review identified that appearance-based interventions may be beneficial for this age group [ 3 ]. The study objectives were to develop and evaluate the feasibility of a secondary school-based appearance focused intervention, including the development and testing of protocols and instruments, as a resource module that could be efficiently integrated into the secondary school science curriculum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When diagnosed early, the rate of survival in 5 years is 92 percent [3]. The later identification of melanoma results in increased treatment expenditure [4]. According to dermatologists, the evaluation of dermoscopic images is frequently time-consuming and an error-prone process [5].…”
Section: Introductionmentioning
confidence: 99%